Successful Treatment of Raynaud's Syndrome with Prostacyclin - Belch, J J F; Newman, P; Drury, J K; Capell, H; Leiberman, P; James, W B; Forbes, C D; Prentice, C R M (Thrombosis and Haemostasis, 1981)
There is evidence to suggest that platelet activation occurs in Raynaud’s syndrome. We evaluated the effect of prostacyclin (PGI2) a potent antiplatelet and vasodilator agent in 5 female patients with Raynaud’s syndrome. Outpatient visits were made at weekly intervals for 4 weeks. At the first visit buffer solution (Wellcome Laboratories) was infused intravenously for 5 hrs, thereafter three five hr infusions of PGI2 at a peak dose of 10 ng/ Kg/min were given. Six weeks after the infusions patients were reviewed. Symptomatic improvement, including healing of ischaemic ulcers, occurred in 4 out of 5 patients. Thermography confirmed an increase in hand temperature after PCI2. Subjective and objective improvement has persisted for at least 6 weeks after the last treatment.
Keywords: Raynaud’s syndrome; Prostacyclin; Thermography in Raynaud’s syndrome